2015
DOI: 10.1186/s12929-015-0196-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor status and Notch inhibition in non-small cell lung cancer cells

Abstract: BackgroundNotch may behave as an oncogene or a tumor suppressor gene in lung cancer cells. Notch receptor undergoes cleavage by enzymes, including γ-secretase, generating the active Notch intracellular domain (NICD). The aim of the present study was to investigate the effect of DAPT, a γ-secretase inhibitor, in non-small cell lung cancer (NSCLC) cells, as well as the impact of epidermal growth factor (EGF) that is over-expressed by NSCLC cells, on Notch signaling. H23, A549, H661 and HCC827 human NSCLC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
2
18
0
3
Order By: Relevance
“…In cancer studies, the Notch pathway has been shown to require active signals from the ERK/MAP kinase pathway downstream of Ras 37 . Moreover EGFR protein levels differentially affected Notch signaling in many lung cancer cell lines 38 . In our study, Notch inhibition significantly reduced FSK-induced proliferation of ADPKD cells and also showed some inhibitory effects on EGF-induced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer studies, the Notch pathway has been shown to require active signals from the ERK/MAP kinase pathway downstream of Ras 37 . Moreover EGFR protein levels differentially affected Notch signaling in many lung cancer cell lines 38 . In our study, Notch inhibition significantly reduced FSK-induced proliferation of ADPKD cells and also showed some inhibitory effects on EGF-induced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that there is a differential response to GSI treatment depending on the EGFR status. NSCLC cell lines with undetectable EGFR protein levels are more sensitive to GSI treatment since both autophagic and apoptotic machineries are activated ( 132 ). EGFR T790M TKI-resistant NSCLC frequently has high IGF-1R expression levels.…”
Section: Notch-related Resistance To Targeted Therapiesmentioning
confidence: 99%
“…Despite being one of the least potent GSIs in preclinical studies ( 155 ), DAPT has proven to be efficacious as single agent in treating NSCLC with altered NOTCH signaling pathway members ( 74 ), in inducing apoptosis and autophagy, preferentially in cells expressing EGFR wild type or without EGFR expression ( 132 ), by inducing cell cycle arrest in G1 and G2/M phases ( 98 ), and reducing the ALDH+ stem cell population ( 156 ). In addition, DAPT can enhance the effects of cisplatin by reducing the CD133+ stem cell subpopulation ( 157 ).…”
Section: Notch Targeting In Nsclcmentioning
confidence: 99%
“…Lung cancer comprises malignant lung tumors characterized by uncontrolled cell growth (24). NSCLC is the primary type of lung cancer and accounts for ~85% of all lung cancer cases (25).…”
Section: Discussionmentioning
confidence: 99%